PELAKSANAAN MAGANG PEMBANGUNAN PROYEK GEDUNG KANTOR PT. MITRAIS - , M. YAFIE WIRDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the construction of office buildings PT.MITRAIS there are many items of work. Each job has a different difficulty level, so to deal with these difficulties in any work the contractor has a team of experts. A team of experts in charge of determining the method implementation to be used to conform to the standards set. As the author had experience in collaboration with a team of experts in the building project. The preparation of the report describes each job is done with jobs in the field and then do an analysis of the data obtained with the existing standards. Data were obtained from direct observations in the field works, interviews, and direct practices. In data analysis, the literature is used to strengthen the study results obtained. In this report, the author discusses and analyzes the implementation of constructing PT.MITRAIS building. This study could be a reference in implementation of the construction of another building that has the specifications and conditions of the same land.